Effect of rare‐earth ion size on elasticity and crack initiation in rare‐earth aluminate glasses. Issue 11 (23rd May 2018) - Rosales‐Sosa, Gustavo A.; Masuno, Atsunobu; Higo, Yuji; Watanabe, Yasuhiro; Inoue, Hiroyuki
Abstract: In oxide glasses, "hardness" and "damage‐tolerance" are usually competing attributes. The main reason for this is that hard glasses usually have closely packed structures compared to those of damage‐resistant glasses. Recent progress on the mechanical properties of alumina‐rich glasses has thrown some light on how to obtain hard and damage‐tolerant glasses. In this work, the elastic properties and indentation behavior of a glass system based on ( R = La, Sm, Gd, Er, Tm, Y), prepared by an aerodynamic levitation technique, was investigated. It was found that the rare‐earth ions exhibited a strong size effect on the mechanical properties of the glasses. The elastic moduli and hardness increased with the packing density and as the ionic radii of the rare‐earth ions decreased. In addition, the resistance to surface damage by indentation increased with larger rare‐earth cations. Our results show that the elastic properties and damage tolerance of rare‐earth aluminate glasses can be tuned depending on the ionic radii of rare‐earth ions. Abstract : Vickers indentation imprints for the 32 R 2 O3 ·68Al2 O3 = La, Sm, Gd, Y, Er, and Tm. Larger ions display higher indentation damage tolerance but lower hardness compared with smaller ions.